2012
DOI: 10.1074/jbc.m112.363622
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophosmin (NPM1/B23) Interacts with Activating Transcription Factor 5 (ATF5) Protein and Promotes Proteasome- and Caspase-dependent ATF5 Degradation in Hepatocellular Carcinoma Cells

Abstract: Background: NPM1 promotes whereas ATF5 inhibits HCC proliferation; NPM1 and ATF5 are regulated in an opposite manner in normal hepatocytes and HCC. Results: NPM1 competes against HSP70 for ATF5 binding and promotes proteasome-and caspase-dependent ATF5 protein degradation. Conclusion: NPM1 is a novel ATF5-interacting protein and abrogates ATF5 function in HCC. Significance: We reveal a mechanism by which NPM1 promotes HCC proliferation and survival via regulation of ATF5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
51
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 57 publications
2
51
0
Order By: Relevance
“…DNA constructs expressing ATF5 full length, ATF5(1-100), ATF5(101-207), ATF5(148-281), ATF5(208-281), and ATF5(K29R) are described previously (8,12,24,25). ATF5(K106R/K107R), ATF5(ΔK212/213), and ATF5(K106R/K107R;ΔK212/213) were created using GFP-ATF5 as template and a QuikChange Site-Directed Mutagenesis Kit (Strategene) as described previously (9).…”
Section: Dnamentioning
confidence: 99%
“…DNA constructs expressing ATF5 full length, ATF5(1-100), ATF5(101-207), ATF5(148-281), ATF5(208-281), and ATF5(K29R) are described previously (8,12,24,25). ATF5(K106R/K107R), ATF5(ΔK212/213), and ATF5(K106R/K107R;ΔK212/213) were created using GFP-ATF5 as template and a QuikChange Site-Directed Mutagenesis Kit (Strategene) as described previously (9).…”
Section: Dnamentioning
confidence: 99%
“…The activating transcription factor 5 (ATF5 or ATFx) is a member of the ATF/CREB transcription factor family. Although ATF5 is known to regulate cell cycle progression [4][5][6][7], cell survival [5][6][7][8][9][10][11][12][13], autophagy [14], cell fate determination [15][16][17] and cellular stress response [13][14][15][16][17][18][19], and it is likely involved in the development of schizophrenia [20][21][22] and chronic lymphocytic leukemia [23], only a few of its targets have been reported and the mechanism of ATF5 function remains largely unknown and occasionally controversial.Previous reports have shown that ATF5 enhances cell survival and proliferation of glioma, breast cancer cells and neuroprogenitor cells [5,[10][11][12]24] while eliciting a G2/M blockade in hepatocellular carcinoma cells [4,6]. ATF5 acts as a pro-survival factor in HeLa and hematopoietic FL5.12 cells [8] but may also increase cisplatin-induced apoptosis through up-regulation of cyclin D3 in HeLa cells [25].…”
mentioning
confidence: 99%
“…The activating transcription factor 5 (ATF5 or ATFx) is a member of the ATF/CREB transcription factor family. Although ATF5 is known to regulate cell cycle progression [4][5][6][7], cell survival [5][6][7][8][9][10][11][12][13], autophagy [14], cell fate determination [15][16][17] and cellular stress response [13][14][15][16][17][18][19], and it is likely involved in the development of schizophrenia [20][21][22] and chronic lymphocytic leukemia [23], only a few of its targets have been reported and the mechanism of ATF5 function remains largely unknown and occasionally controversial.…”
mentioning
confidence: 99%
See 2 more Smart Citations